Direct Observation of the Collision of Single Pt Nanoparticles onto Single‐Crystalline Gold Nanowire Electrodes. Issue 15 (21st July 2016) - Shin, Changhwan; Bae, Hyeonhu; Kang, Mijeong; Kim, Bongsoo; Kwon, Seong Jung
Abstract: We observed the collision of single Pt nanoparticles (NPs) onto an Au nanowire (NW) electrode by using electrocatalytic amplification. Previously, such observations had typically been performed by using a microscale disk‐type ultramicroelectrode (UME). The use of a NW electrode decreased the background noise current and provided a shielding effect, owing to adsorption of the NPs onto the insulating sheath. Therefore, the transient current signal that was caused by the collision of single NPs could be more clearly distinguished from the background current by using a NW electrode instead of a UME. Furthermore, the use of a NW electrode increased the collisional frequency and the magnitude of the transient current signal. The experimental data were analyzed by using a theoretical model and a random walk simulation model. Abstract : Nanoparticle and nanowire electrode : The collision of single Pt nanoparticles onto an Au nanowire electrode was observed by using electrocatalytic amplification. Previously, such observations had typically been performed by using a microscale disk‐type ultramicroelectrode. The use of a nanowire electrode decreased the background noise current and provided a shielding effect, owing to adsorption of the NPs onto the insulating sheath.